Pengembangan Lembar Kerja Praktikum Keanekaragaman Hayati untuk Meningkatkan Pemahaman Konsep dan Sikap Peduli Lingkungan - Fita Kharisma Ameliyah; Hana Delia; Hana Marva Aulia; Ade Suryanda; Fitria Pusparini (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This research aims to develop a biodiversity Practicum Worksheet (LKP) that is oriented towards improving students' understanding of environmental concepts and attitudes. The research uses the Research and Development (R&D) method with a 4D model that is limited to the development stage. The development stages include analysis of learning needs, design of LKP structures, and product validation by experts. Data was obtained from the validation results and analyzed descriptively to determine the feasibility level of the product. The validation results showed that the LKP developed was in the category of feasible use with a feasibility percentage of 77%. However, there are several aspects that still need improvement, especially in the deepening of the material, linguistic clarity, as well as the completeness and clarity of practicum tools and materials. The LKP developed integrates contextual practicum activities, data analysis, and reflection on environmental care attitudes, so that it has a practical contribution as a biology learning tool that is not only procedural, but also encourages the linkage between observation results and the concept of biodiversity. Thus, this LKP has the potential to support more meaningful learning after improvements are made according to the validator's recommendations.